Incomplete diversification and asset pricing - Robert Elliott; Dilip Madan; Frank Milne (Queen's University, Department of Economics, 2002)
Investors in equilibrium are modeled as facing investor specific risks across the space of assets. Personalized asset pricing models reflect these risks. Averaging across the pool of investors we obtain a market asset pricing model that reflects market risk exposures. It is observed on invoking a law of large numbers applied to an infinite population of investors, that many personally relevant risk considerations can be eliminated from the market asset pricing model. Examples illustrating the effects of undiversified labor income and taste specific price indices are provided. Suggestions for future work on asset pricing include a need to focus on identifying and explaining investor specific risk exposures.
Keywords: G12; G13; 330; Diversification; Asset Pricing; Investor specific risks; Kapitalmarkttheorie; Wertpapieranalyse; Portfolio-Management; Risiko; Anlageverhalten; Theorie